The Early Tourist Guidebooks to the Dutch East Indies and Malaya in the Nineteenth and Twentieth Century - Sunjayadi, Achmad (Paradigma: Jurnal Kajian Budaya, 2019)
At the end of the nineteenth century until the beginning of the twentieth century, International tourists have begun visiting the Dutch East Indies and Malaya. Therefore, guidebooks about the Dutch East Indies and Malaya were published for travellers and tourists. Using the historical method, this article discusses which information, how and why the information presented in the early tourist guidebooks. The result shows that the guidebooks provide various information not only about the objects that can be visited, but also about natural scenery, peoples, culinary, flora, fauna, and customs in the regions. They presented in a long narrative and practical text with illustrations. The illustrations in the Indies’ tourist guidebooks are more varied and accentuate nature and culture compared to Malaya’s guidebooks. Both of them presented exotics objects with the aim to attract western tourists in particular.